Pemetaan Arah Desain Rice box untuk Pengguna Di Indonesia - Wildan Aulia (JOURNAL OF APPLIED SCIENCE (JAPPS), 2020)
In 2011 and 2016, the author had been designed a rice box based on user aspect. The result indicated the change of rice box product design in form of dimension/ load capacity. This indication then followed by continued study in order to find the comprehensive design of rice box development. This research is focused on design mapping based on design direction of rice box that had been done in 2011, 2016 and 2019, also perceptual mapping method on existing rice box products. The aim is to find the tendency user preference to rice box design. The result showed that the significant value for user preference is rice box with capacity of 12 kg and slowly leave the rice box with capacity of 30 kg. This study also argued that there is an implication of rice consumption changing. The result is hopefully could become the reference in rice box design based on mapping result that can be applied by industrial stakeholder.